Association of dietary vitamin intake with gallstone risk in US adults: a cross-sectional NHANES study - Pinchu Chen; Chenfenglin Yang; Jieru Ding; Yao Li; Wen Hu; Qifan Zhang (European Journal of Medical Research)
Abstract Background Gallstones represent a significant global health challenge, impacting both the healthcare system and the broader socio-economic landscape. Despite their prevalence, the relationship between vitamin intake and gallstone development remains underexplored, which this research aims to address. Methods A total of 4,628 participants from the 2017–2020 National Health and Nutrition Examination Survey (NHANES) database were included in this study. Data on gallstones were collected through self-reported questionnaires. We conducted a multifactorial logistic regression analysis to explore the association between vitamin intake and the prevalence of gallstones. Various subgroups were analyzed, and potential interactions were tested. Results Female gender, advanced age, obesity, and hyperlipidemia were identified as risk factors associated with a higher prevalence of gallstones. Higher dietary intake of vitamin B6 (OR: 0.73, 95% CI 0.61–0.88), niacin (OR: 0.96, 95% CI 0.95–0.98) and vitamin E (OR: 0.96, 95% CI 0.94–0.99) was associated with reduced gallstone risk in unadjusted models. However, after full adjustment (Model 3), only niacin retained marginal significance (OR: 0.98, 95% CI 0.97–1.00, p = 0.035). Restricted cubic spline analyses suggested potential linear relationships between niacin and gallstone risk. Conclusions The findings from the NHANES database indicate that increased dietary intake of vitamin B6, niacin, and vitamin E may lower the risk of gallstones in the U.S. population. The mechanisms underlying the role of vitamins in gallstone formation warrant further exploration.